2017
DOI: 10.1111/jai.13318
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of body composition and sensory quality of wild and farmed whitefish (Coregonus macrophthalmus [Nüsslin, 1882])

Abstract: Summary This study compared the body composition (fillet yield, chemical composition and lipid quality of fillets) and sensory quality of captured wild (by gillnet in August 2011) with experimentally raised farmed (reared in concrete flow‐through raceways, average water temperature 10 ± 3°C) whitefish, Coregonus macrophthalmus, from Lake Constance. The study was conducted in 2011 using 28 wild and 24 farmed market‐sized fish of approximately equal total lengths (25.1 ± 1.21 and 25.6 ± 1.28 cm). Farmed female C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Thirty six fatty acids were reported, including sixteen SFA, nine MUFA and eleven PUFA (Table 2). Similarly to results obtained by several authors (KAYA & ERDEM 2009;YEŞILAYER & GENÇ 2013, OZ & DIKEL, 2015GOEBEL et al, 2016;GULLER et al, 2017) the largest amounts of total SFA were reported both in wild and farmed brown trout. In the present study palmitic acid was identified as the predominant SFA in all trout, being the highest content reported in farmed brown trout (16.64g/100g of total fatty acids).…”
Section: Resultssupporting
confidence: 84%
“…Thirty six fatty acids were reported, including sixteen SFA, nine MUFA and eleven PUFA (Table 2). Similarly to results obtained by several authors (KAYA & ERDEM 2009;YEŞILAYER & GENÇ 2013, OZ & DIKEL, 2015GOEBEL et al, 2016;GULLER et al, 2017) the largest amounts of total SFA were reported both in wild and farmed brown trout. In the present study palmitic acid was identified as the predominant SFA in all trout, being the highest content reported in farmed brown trout (16.64g/100g of total fatty acids).…”
Section: Resultssupporting
confidence: 84%
“…These discrepancies found among different research results might be related with both with fish intrinsic and extrinsic features (geographical origin, genotype, season, sexual maturation, age, feeding, water quality, presence of disease and parasites), which influence fish chemical composition and, consequently, fish sensory variables (taste, texture, and appearance) which, in turn, determine fish quality, consumer acceptance and commercialization (Grigorakis, 2007;Green-Petersen & Hyldig, 2010;Oken et al, 2012;Claret et al, 2014;Suomela et al, 2016). Farmed fish sensorial quality and acceptance is also influenced phenotypic responses to the rearing environment (Goebel et al, 2017). Green-Petersen & Hyldig (2010) found out that even fish from the same aquaculture batch can present considerable variation in fish body chemical composition.…”
Section: Sensory Acceptability Of the Fish Samplesmentioning
confidence: 99%